Educomunicação: integração midiatica da radio El Chasque na comunidade Cerro Pelado, Uruguai - Pauli, Eduardo (2016)
We live in an era of technological change and this study addresses the challenge for schools to enter the new information and communication technologies in the school environment and use these new tools for learning. The object of this research is Radio EL Chasque FM 91.9MHz, its historicity as a educommunication project with the school Vale La Pena, Liceo Rural y Comunitario of Cerro Pelado in Rivera / Uruguay. The aim of this study is to understand the use of ICTs used in radio programs, and the importance of this form of communication for the development of the rural community of Cerro Pelado. As a result points to the involvement and use of ICT in conjunction with the educational communication and the use of digital tools to facilitate more effective communication, especially when one realizes the need for communication between students who do extracurricular discipline involving the community radio, Identified as a facilitator of this communication for the construction of radio and dissemination of information programs, the use of ICT, which thus exerts a media and educommunication mediation, aiming to improve the use of tools increased the effectiveness of the parties. In conclusion, it reinforces the effectiveness of educational communication project through the radio transformation process as a component discipline of the school's educational project, allowing the integration between students and the community, and especially autonomy, because the radio is run by students, the teacher acts as a counselor, who together learn and teach in theory and practice simultaneously.l.